2008
DOI: 10.1111/j.1467-9450.2008.00662.x
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the gender typing of management characteristics in an egalitarian context

Abstract: The present studies sought to investigate what kind of stereotypes are used in Sweden to describe male and female managers, and whether gender-neutral characteristics are used in the description of requisite management characteristics. In Study 1, participants answered open-ended questions on good, bad, female and male management. Requisite management characteristics showed a greater resemblance to the descriptions of female managers than male. In Study 2, female managers were rated more positively than men, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 57 publications
0
7
0
Order By: Relevance
“…Gender bias in favor of men is frequently perceived by women, but often unobserved by male managers and subordinates (Ayman et al, 2009;Elacqua et al, 2009). Studies investigating management stereotypes in Sweden have found both gender typing of management stereotypes in favor of men (Fullagar et al, 2003) and more positive ratings of the female manager stereotype than the male manager stereotype (Kusterer, 2008). Consequently, in the current study, we needed to examine stereotypical beliefs of both men and women, as well as the existence of perceived gender bias in management.…”
Section: The Present Studymentioning
confidence: 96%
See 2 more Smart Citations
“…Gender bias in favor of men is frequently perceived by women, but often unobserved by male managers and subordinates (Ayman et al, 2009;Elacqua et al, 2009). Studies investigating management stereotypes in Sweden have found both gender typing of management stereotypes in favor of men (Fullagar et al, 2003) and more positive ratings of the female manager stereotype than the male manager stereotype (Kusterer, 2008). Consequently, in the current study, we needed to examine stereotypical beliefs of both men and women, as well as the existence of perceived gender bias in management.…”
Section: The Present Studymentioning
confidence: 96%
“…To measure stereotypes of male and female managers and perceptions of participants' own managers, items generated in a previous study (Kusterer, 2008) were used. In that study, Swedish participants were first asked to generate items on good and bad management in general, and then, on a separate page, the common cultural conception, that is, the stereotypes, of male and female managers.…”
Section: Questionnaire Constructionmentioning
confidence: 99%
See 1 more Smart Citation
“…One important line of research in the study of major barriers to women's entry into management has focused on gender stereotyping of managerial position (e. g., Duehr & Bono, ; Kusterer, ; Powell, Butterfield & Parent, ; Schein & Mueller, ; Schein, Mueller, Lituchy & Liu, ; Sczesny, ; Sczesny, Bosak, Neff & Schyns, ; Sümer, ). The general purpose of these studies has been to determine the relationship between gender stereotyping and requisite management characteristics.…”
Section: Gender‐typing Of Managerial Rolesmentioning
confidence: 99%
“…Gender-typing of managerial positions has been offered as one possible explanation for women's underrepresentation (e.g., Schein, 1973Schein, , 2001. Gender-typing refers to the association of a certain role with either gender (Kusterer, 2008). This paper attempts to expand on the literature regarding this topic.…”
Section: Introductionmentioning
confidence: 99%